2009 IEEE International Symposium on Information Theory 2009
DOI: 10.1109/isit.2009.5205977
|View full text |Cite
|
Sign up to set email alerts
|

Storage coding for wear leveling in flash memories

Abstract: Abstract-Flash memory is a nonvolatile computer memory comprised of blocks of cells, wherein each cell is implemented as either NAND or NOR floating gate. NAND flash is currently the most widely used type of flash memory. In a NAND flash memory, every block of cells consists of numerous pages; rewriting even a single page requires the whole block to be erased and reprogrammed. Block erasures determine both the longevity and the efficiency of a flash memory. Therefore, when data in a NAND flash memory are reorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…The block erasure property of flash memories affects not only rewriting and cell programming, but also data movement. In [22], it is shown that by appropriately using coding, the number of erasures needed for moving data among n NAND flash blocks can be reduced by a factor of O(log n). The rewriting codes and the rank modulation scheme are useful not only for flash memories, but also for other constrained memories.…”
Section: Extended Information Theoretic Resultsmentioning
confidence: 99%
“…The block erasure property of flash memories affects not only rewriting and cell programming, but also data movement. In [22], it is shown that by appropriately using coding, the number of erasures needed for moving data among n NAND flash blocks can be reduced by a factor of O(log n). The rewriting codes and the rank modulation scheme are useful not only for flash memories, but also for other constrained memories.…”
Section: Extended Information Theoretic Resultsmentioning
confidence: 99%
“…Therefore, it is critical to minimize the number of erasures when data are reorganized [2]. This leads to the data movement problem, which has been studied in [3], [5]. Although data movement is common in all storage systems, the unique block erasure property of flash memories calls for special solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In the data movement problem [3], [5], there are n blocks storing data, where every block has m pages. The nm pages of data need to be switched among the n blocks with specified destinations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations